2023
DOI: 10.1007/s00170-023-11001-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the lead angle limit to achieve required surface roughness in ball-end milling

Abstract: When milling generally shaped surfaces with a ball-end milling tool, machined surface roughness and accuracy as well as machining productivity are often monitored. Improving one of these parameters often causes a decrease in the other monitored parameters. Therefore, knowing possible ways of influencing these parameters is important for achieving the optimum result, if possible, in all requirements. A deep understanding of how some technological parameters influence finished surface roughness is still lacking,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…When the inclination angle was 15°, the surface roughness could be reduced by 35% compared to the absence of an inclination angle. Taking a ball-end tool as the research object, Pesice et al [ 43 ] investigated the effect of the lead angle on roughness. They found that the roughness of the workpiece decreased as the lead angle increased (0–30°).…”
Section: Introductionmentioning
confidence: 99%
“…When the inclination angle was 15°, the surface roughness could be reduced by 35% compared to the absence of an inclination angle. Taking a ball-end tool as the research object, Pesice et al [ 43 ] investigated the effect of the lead angle on roughness. They found that the roughness of the workpiece decreased as the lead angle increased (0–30°).…”
Section: Introductionmentioning
confidence: 99%